Role of nocturnal rostral fluid shift in the pathogenesis of obstructive and central sleep apnoea - White, Laura H (Blackwell Science Inc, 2013)
Obstructive sleep apnoea (OSA) is common in the general population and increases the risk of motor vehicle accidents due to hypersomnolence from sleep disruption, and risk of cardiovascular diseases owing to repetitive hypoxia, sympathetic nervous system activation, and systemic inflammation. In contrast, central sleep apnoea (CSA) is rare in the general population. Although their pathogenesis is multifactorial, the prevalence of both OSA and CSA is increased in patients with fluid retaining states, especially heart failure, where they are associated with increased mortality risk. This observation suggests that fluid retention may contribute to the pathogenesis of both OSA and CSA. According to this hypothesis, during the day fluid accumulates in the intravascular and interstitial spaces of the legs due to gravity, and upon lying down at night redistributes rostrally, again owing to gravity. Some of this fluid may accumulate in the neck, increasing tissue pressure and causing the upper airway to narrow, thereby increasing its collapsibility and predisposing to OSA. In heart failure patients, with increased rostral fluid shift, fluid may additionally accumulate in the lungs, provoking hyperventilation and hypocapnia, driving [Image: see text] below the apnoea threshold, leading to CSA. This review article will explore mechanisms by which overnight rostral fluid shift, and its prevention, can contribute to the pathogenesis and therapy of sleep apnoea.